Competence Based Learning Implementation for Public Administration Student Programs to Improve Competency in Facing Industrial Era 4.0 - Dewi Maharani (Iapa Proceedings Conference, 2019)
In line with the development of the industrial era 4.0, learning should be able to produce students who are not only capable of material content, but must also have soft skills to support skills or competencies for students. Today the need for the world of work can not only rely on muscle, but the ability of the brain to be something that is a fundamental need. Competencies applied to learning are in accordance with 21st century competencies, namely the ability to communicate, collaborate, think critically and problem solving, and have creativity and innovation. The method used is descriptive qualitative research sources are primary and secondary. Data processing techniques are carried out through four stages namely data reduction, data presentation, comparative analysis, and drawing conclusions. Data collection methods used are observation, interviews, and documentation. The results showed that the application of competency-based learning with communication competencies was inadequate, collaborative competencies were adequate, critical thinking and problem solving were inadequate, and creative and innovative competencies were inadequate. The implication of this research is that students must further improve their communication skills both through oral and written, increase critical power and always think solutively in solving problems, and always try to innovate to explore creativity in each individual.